Respiratory Support of Infants With Congenital Diaphragmatic Hernia - Williams, Emma; Greenough, Anne (Frontiers in Pediatrics, 2021)
Optimisation of respiratory support of infants with congenital diaphragmatic hernia (CDH) is critical. Infants with CDH often have severe lung hypoplasia and abnormal development of their pulmonary vasculature, leading to ventilation perfusion mismatch. It is vital that lung protective ventilation strategies are employed during both initial stabilisation and post-surgical repair to avoid ventilator induced lung damage and oxygen toxicity to prevent further impairment to an already diminished gas-exchanging environment. There is a lack of robust evidence for the routine use of surfactant therapy during initial resuscitation of infants with CDH and thus administration cannot be recommended outside clinical trials. Additionally, inhaled nitric oxide has been shown to have no benefit in reducing the mortality rates of infants with CDH. Other therapeutic agents which beneficially act on pulmonary hypertension are currently being assessed in infants with CDH in randomised multicentre trials. The role of novel ventilatory modalities such as closed loop automated oxygen control, liquid ventilation and heliox therapy may offer promise for infants with CDH, but the benefits need to be determined in appropriately designed clinical trials.